Life on the rocks: unexpected enzyme activity of the extremophilic black fungus Knufia chersonesos - Mihalyi, Sophia; Zimmermann, Christian; Quartinello, Felice; Tesei, Donatella; Mach-Aigner, Astrid R.; Guebitz, Georg; Ribitsch, Doris (Frontiers in Bioengineering and Biotechnology, 2026)
Knowledge about extremophile organisms and their survival strategies could be of great value for various industrial applications including biological plastics recycling. The black fungus Knufia chersonesos inhabits extreme environments such as rocks and therefore produces specific enzymes that function under harsh conditions. A cutinase (Kc_Cut) and a lipase (Kc_Lip) identified via proteomics-based screening in the secretome of K. chersonesos grown on poly (butylene-adipate-co-terephthalate) (PBAT) as carbon sources were recombinantly expressed in Komagataella phaffii and Trichoderma reesei, respectively, for further characterization. The purified enzymes showed a specific activity of 83 ± 1 and 0.23 ± 0.02 U mg-1 on para-nitrophenylbutyrate (p-NPB) as substrate, respectively. Optimum conditions of Kc_Cut were evaluated through activity measurements on p-NPB and resulted in 50 °C, pH 8 and 100 mM potassium phosphate buffer. Incubation with PBAT powder for 72 h resulted in the release of 17 ± 1 µM of terephthalic acid (Ta) by Kc_Cut while the Kc_Lip liberated the trimer BTaB. This indicated a cooperative action of the two enzymes which was confirmed by hydrolysis of BTaB by Kc_Cut and provides valuable insight into the metabolic potential and adaptability of K. chersonesos.